Anti-resonant reflecting acoustic rib waveguides for strong opto-acoustic interaction - Thomas J. Dinter; Mikołaj K. Schmidt; Michael J. Steel (APL Photonics)
Few known material systems can simultaneously guide optical and elastic fields through total internal reflection. This natural limit has restricted the realization of strong optoacoustic effects to highly specialized and purpose-built platforms, which employ either exotic materials or complex waveguide designs. Here, we apply the concept of Anti-Resonant Reflecting Acoustic Waveguides (ARRAWs) as a potential solution to this issue. ARRAWs confine the elastic field to a high-elastic-velocity core via the anti-resonances of a cladding layer of lower elastic velocity. We numerically study the appearance and dispersion of ARRAW-guided modes in a conventional silicon-on-insulator rib waveguide geometry. Applying the technique to the problem of efficient backward stimulated Brillouin scattering, we predict that ARRAW guidance, in conjunction with conventional optical confinement, can produce Brillouin gains comparable with those of more exotic geometries.